2003
DOI: 10.1097/00005768-200301000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Activation Strategies at the Knee during Running and Cutting Maneuvers

Abstract: In PP conditions, activation patterns appear to be selected to support the external loads experienced at the knee, e.g., medial muscles activated to resist applied valgus moments. Under UN conditions, there was no selective activation of muscles to counter the external knee load, with generalized co-contraction being the activation pattern adopted. These findings have implications for the etiology of noncontact knee ligament injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
302
2
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 311 publications
(313 citation statements)
references
References 18 publications
7
302
2
2
Order By: Relevance
“…However, published reports suggest that manoeuvres incorporated in shuttle running may increase net muscle activation compared to forward running (9). In contrast, the SST prediction has been based on fairly similar running modes (i.e.…”
Section: Results (2 Nd Heading In Importance)mentioning
confidence: 99%
“…However, published reports suggest that manoeuvres incorporated in shuttle running may increase net muscle activation compared to forward running (9). In contrast, the SST prediction has been based on fairly similar running modes (i.e.…”
Section: Results (2 Nd Heading In Importance)mentioning
confidence: 99%
“…During sidestepping, Besier and colleagues [36] identified specific muscle activation patterns they suggested stabilized the knee against the large and complex external loads. However, their measures of stabilization were derived directly from surface EMG [36], and were thus indirect measures of muscle action that may not have reflected the actual mechanical stabilization of the knee.…”
Section: Discussionmentioning
confidence: 99%
“…During sidestepping, Besier and colleagues [36] identified specific muscle activation patterns they suggested stabilized the knee against the large and complex external loads. However, their measures of stabilization were derived directly from surface EMG [36], and were thus indirect measures of muscle action that may not have reflected the actual mechanical stabilization of the knee. Our results indicated that muscle was the primary contributor to the tibiofemoral contact forces during running and sidestepping (>75% of compartmental contact loading), and were comparable to the relative contributions made by the external loads during walking (40-65%).…”
Section: Discussionmentioning
confidence: 99%
“…22 Specifically, the CCI was quantified as the ratio of the averaged normalized flexor EMG (ST, BFL, MG, and LG) to the averaged normalized extensor EMG (VM, VL, and RF) multiplied by the averaged normalized EMG of all muscles during the deceleration phase of the drop-land task. During the deceleration phase of the dropland task, the averaged normalized extensor EMG was always greater than the averaged normalized flexor EMG.…”
Section: Kinematic and Emg Variablesmentioning
confidence: 99%